"2y^2+4x y\\frac{ dy}{dx} + xe^{xy} \\frac{dy}{dx} + 2y\\frac{ dy}{dx}=-ye^{xy}"
"(4x y + xe^{xy} + 2y)\\frac{ dy}{dx}+2y^2+ye^{xy}=0"
"(2y^2+ye^{xy})dx+(4x y + xe^{xy} + 2y) dy=0"
"\\frac{\\partial}{\\partial x}(4x y + xe^{xy} + 2y)=4y+e^{xy}+xye^{xy}"
"\\frac{\\partial}{\\partial y}( 2y^2 + ye^{xy})=4y+e^{xy}+xye^{xy}"
Since "\\frac{\\partial}{\\partial x}(4x y + xe^{xy} + 2y)=\\frac{\\partial}{\\partial y}( 2y^2 + ye^{xy})", there exists a function "U=U(x,y)" such that "dU=(4x y + xe^{xy} + 2y) dy+(2y^2+ye^{xy})dx." Therefore, "\\frac{\\partial U}{\\partial x}=2y^2 + ye^{xy}" and "\\frac{\\partial U}{\\partial y}=4x y + xe^{xy} + 2y".
"U(x,y)=\\int(2y^2 + ye^{xy})dx=2y^2x+e^{xy}+C(y)".
"4xy + xe^{xy}+2y=\\frac{\\partial U}{\\partial y}=\\frac{\\partial }{\\partial y}(2y^2x+e^{xy}+C(y))=4xy+xe^{xy}+C'(y)"
Therefore, "C'(y)=2y". So "C(y)=y^2+C".
We conclude that the general solution of the differential equation is the following:
"2y^2x+e^{xy}+y^2=C"
Comments
Leave a comment